Konsep Kesehatan Mental Perspektif Abu Zaid Al-Balkhi Relevansi terhadap Pendidikan Agama Islam - Sabilatur Rosada; Saiful Arif (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Mental health is an essential element in education, particularly in Islamic Religious Education, as it plays a role in shaping students' emotional, spiritual, and behavioral development. This study carefully examines the concept of mental health proposed by Abu Zaid Al-Balkhi and evaluates its relevance within contemporary Islamic religious education. Employing a qualitative approach based on literature analysis and a conceptual-analytical method, the primary source is Al-Balkhi's work Mashalih al-Abdan wa al-Anfus, supported by relevant scholarly literature. The findings indicate that Al-Balkhi defines mental health not merely as the absence of disorders, but as a dynamic state of balance encompassing physical, psychological, social, and spiritual aspects. This balance is achieved through cognitive management, emotional control, and the reinforcement of spiritual values. Al-Balkhi's thought aligns with modern cognitive therapy, particularly in transforming negative thinking patterns into constructive ones. Values such as gratitude, patience, and self-control play significant roles in maintaining mental well-being. This study contributes by offering a conceptual integration of Al-Balkhi's ideas into Islamic Religious Education through a holistic learning approach that emphasizes not only intellectual domains but also the development and well-being of students' mental health. Thus, this framework is relevant as a foundation for developing integrative education tailored to current student needs